Butterfly conservation in South-Eastern Australia progress and prospects - New, Tim R. (Springer eBooks., 2011)
This survey of the development of butterfly conservation in an important, largely endemic and highly threatened regional fauna of Australia demonstrates how lessons from elsewhere have been applied and developed in a relatively poorly known fauna, in which conservation targets range from single subspecies to entire biotopes and communities. Principles and practical programmes are discussed, and much hitherto scattered information is brought together in a synthesis that will be of considerable interest to ecologists, conservation biologists, and butterfly conservation practitioners in other parts of the world.